Social Structure and Interactions Differentially Shape Aerotolerant and Anaerobic Gut Microbiomes in a Cooperative Breeding Species - Chuen Zhang Lee; Sarah F. Worsley; Terry Burke; Jan Komdeur; Falk Hildebrand; Hannah L. Dugdale; David S. Richardson (Molecular Ecology, 2026)
Social transmission of microbes has profound impacts on disease epidemiology and host health. However, how social factors influence gut microbiome (GM) transmission in wild populations is not well understood. Here, we use a wild population of the Seychelles warbler, a facultative cooperatively breeding passerine, to determine whether cooperative breeding behaviour influences the GM. Specifically, we hypothesise that close social interactions as part of cooperative breeding should encourage the sharing of anaerobic microbes, which may be less likely to transmit indirectly through the environment. We found that GM composition was more similar within versus between social groups, and this effect was driven by sharing both aerotolerant and anaerobic bacterial genera. As predicted, the similarity of anaerobic, but not aerotolerant, GM communities between pairs of individuals within a group was positively correlated with the strength of their social interactions (defined by their cooperative breeding status). Specifically, anaerobic GM composition was more similar between pairs of individuals that cooperate at the nest (dominant breeders and dominant‐helper pairs) than for non‐cooperative pairs (involving non‐helping subordinate individuals). This is likely because breeders and helpers directly interact while caring for offspring at a nest. This work reveals how cooperative social interactions lead to microbial transmission and thus contribute to shaping specific components of a host's gut microbiome.